Władysława Spiżewska. Wyemancypowana pionierka bydgoskiej fotografii zawodowej (Kronika Bydgoska, 2016)
The main topic of the article is description of Władysława Spiżewska, the first Polish woman who opened her own photographic studio in Bydgoszcz, whose personality and work had been completely forgotten. This study results from extensive research of the author on Bydgoszcz female photographers. The article presents a brief history of the Margraf family, from which Spiżewska originated. It also describes the specificity of the Bydgoszcz market of photographic services during the 1920s, photographic techniques popular in that time, the look of photographic studio and photographs taken by the central figure of the article. The author of the article takes the reader through the life of Władysława Spiżewska from her birth, two marriages, including one with her student twenty years her junior, difficulties related to running of the studio, and closing of her business in Bydgoszcz.